PERLINDUNGAN HUKUM ATAS PENGGUNAAN HASIL FOTO DARI FOTOGRAFER SEBAGAI MEDIA PROMOSI DI MEDIA SOSIAL INSTAGRAM - Syaiful Waliyadin; Zulfikar Jayakusuma; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Copyright is part of a set of rights which is called Intellectual Property Rights. Intellectual Property Rights is covering an area of law that concerns the rights of jurisdiction over the works or creations if the results of human thought interlocked with interests are economic and moral. This study aims to determine the legal protection of the use of the results of the photo of a photographer where the results of the photos from photographers such as social media, namely Instagram, based on Law Number 28 of 2014 On Copyright and also remedies that can be done by photographers as the victim for the use of the photos as a media promotion social media Instagram.This type of research is classified into legal research methods sociological because the purpose of this study was to see the level of synchronization of the law based on copyright law Number 28 of 2014 on Copyright, as well as the laws and regulations related to the reality of life in the community. The source of the data used is primary data, secondary data, and tertiary data by performing data collection techniques interviews, literature review, and data analysis.The results of this study two main things can be concluded First, the Implementation of the protection of the rights of the copyright photos in Pelalawan not run as outlined in the copyright law. It can be known from the persistence of violations related to copyright, violation of this even be done by the government, where they should participate in implementing the protection of copyright, what's copyright a work that comes from their area. Second, Efforts can be taken by the copyright holders of the photo against the violation of use of the photos is to use two ways, namely in litigation or through the Commercial Court and non-litigation such as mediation, conciliation, negotiation, and conciliation.Keywords: Legal Protection – Copyright– Social Media